Politics in territory. Gender, migrations and the sustainability of life in Argentina - María José Magliano; Sofía Arrieta (Íconos)
The present article attempts to recapture the importance of the category of “life sustainability “ as a helpful tool in the study of the experiences and practices of Peruvian women living in the Argentinean city of Cordoba. This women belong into the lower-income segment of the local population and dwell in peripheral and relegated urban spaces. In order to achieve this goal, the text harnesses two key theoretical contributions: feminist economic theory and the available findings of current research on the dynamic social construction of citizenship. The study is based on field work where a qualitative longitudinal approach was employed. In-depth interviews were combined with participant observation methodology. The main result of the research shows that the women´s life-sustainability practices are able not only to secure family and neighborhood reproduction, but also have a tangible and positive impact on the exercise of citizenship. These practices condense a know-how that is built and fed back in time, going back to the pre-migration context and is supported by specific migratory, occupational and urban trajectories. In the conclusion, the article highlights the analytical potency of the concept of “life-sustainability” as an analytical category that can be helpful in understanding how migrants use strategies of collective organization centered on community care, in order to achieve political agency within a given territory.